Troubled Partnership U.S.-Turkish Relations in an Era of Global Geopolitical Change - Larrabee, F. Stephen (RAND Corporation, 2010)
U.S.-Turkish relations, long a vital element of U.S. policy, have seriously deteriorated in recent years. However, the arrival of a new U.S. administration offers an opportunity to repair recent fissures. Priority should be given to harmonizing policy toward Iraq and the Middle East as well as Central Asia and the Caucasus.